2017
DOI: 10.1371/journal.pntd.0005272
|View full text |Cite
|
Sign up to set email alerts
|

The Antiviral RNAi Response in Vector and Non-vector Cells against Orthobunyaviruses

Abstract: BackgroundVector arthropods control arbovirus replication and spread through antiviral innate immune responses including RNA interference (RNAi) pathways. Arbovirus infections have been shown to induce the exogenous small interfering RNA (siRNA) and Piwi-interacting RNA (piRNA) pathways, but direct antiviral activity by these host responses in mosquito cells has only been demonstrated against a limited number of positive-strand RNA arboviruses. For bunyaviruses in general, the relative contribution of small RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
109
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(118 citation statements)
references
References 77 publications
7
109
2
Order By: Relevance
“…The clear Ping‐Pong signature of RVFV‐specific 27‐28‐nt‐long vpiRNAs was confirmed by a more recent study, including the typical 10 nt overlap between the sense/antisense pairs of vpiRNAs (Dietrich, Jansen, et al, ). Infection with BUNV showed that, apart from siRNAs, also virus‐specific piRNAs (24–30 nt) were produced, possessing a clear vpiRNA signature similar to the one described by Leger et al () (Dietrich, Shi, et al, ). Interestingly, variabilities between the three viral genome segments exist, with regard to: a) their representation in the vpiRNAs pool, with M being the predominant vpiRNA source followed by S and with L having low vpiRNA reads, and b) their strand bias, with M‐ and S‐derived vpiRNAs being biased for the (sense) antigenome, and L‐specific ones for the (antisense) genome strand (Dietrich, Jansen, et al, ; Dietrich, Shi, et al, ).…”
Section: Antiviral Role Of Pirnassupporting
confidence: 53%
See 2 more Smart Citations
“…The clear Ping‐Pong signature of RVFV‐specific 27‐28‐nt‐long vpiRNAs was confirmed by a more recent study, including the typical 10 nt overlap between the sense/antisense pairs of vpiRNAs (Dietrich, Jansen, et al, ). Infection with BUNV showed that, apart from siRNAs, also virus‐specific piRNAs (24–30 nt) were produced, possessing a clear vpiRNA signature similar to the one described by Leger et al () (Dietrich, Shi, et al, ). Interestingly, variabilities between the three viral genome segments exist, with regard to: a) their representation in the vpiRNAs pool, with M being the predominant vpiRNA source followed by S and with L having low vpiRNA reads, and b) their strand bias, with M‐ and S‐derived vpiRNAs being biased for the (sense) antigenome, and L‐specific ones for the (antisense) genome strand (Dietrich, Jansen, et al, ; Dietrich, Shi, et al, ).…”
Section: Antiviral Role Of Pirnassupporting
confidence: 53%
“…Regarding Piwi4, an important but not yet specified role in antiviral defense is proposed for it in the Ae. aegypti Aag2 cell line (Dietrich, Shi, et al, ). When infected with the (+) RNA virus Semliki Forest virus (SFV), silencing of piwi4 enhanced not only viral replication but also virion production, while it had no effect on vpiRNA production (Schnettler, Donald, et al, ; Varjak et al, ; Varjak, Donald, et al, ; Varjak, Maringer, et al, ).…”
Section: Antiviral Role Of Pirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…These vpiRNAs had the typical ping-pong signature (U 1 -A 10 ) of secondary piRNAs. This signature has also been found in vpiRNAs produced during alphavirus (76) and bunyavirus (63, 77) infections, but not in vpiRNA-like small RNAs in most flaviviruses, such as DENV (78), ZIKV (79, 80) and an insect-specific flavivirus (81). We found a higher proportion of small RNAs from Aag2- w MelPop-CLA cells that mapped to AeAV are vpiRNAs (about 50%) as compared to less than 10% vsiRNAs.…”
Section: Discussionmentioning
confidence: 93%
“…Through the identification of ASFLI-specific siRNA and piRNA in the ticks and tick cells, we provide data suggesting that the ASFLI-elements might in fact represent an RNAi-based defence against ASFV infection in Ornithodoros ticks. Both siRNA and piRNA are known as major regulation factors of transcription, transposon suppression and defence against viral pathogens (35)(36)(37)(38). Although, for ticks the known arsenal of antiviral mechanisms includes protection by RNAi (39), the role of EVEs in RNAi and protection against viral pathogens has never been reported.…”
Section: Discussionmentioning
confidence: 99%